PENGARUH LEVERAGE DAN PENGUNGKAPAN TATA KELOLA TERHADAP EARNING MANAGEMENT DENGAN TAX AVOIDANCE SEBAGAI VARIABEL MODERASI PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2018-2021 - Timothy Tjandra; Sukrisno Agoes (Fakultas Ekonomi Universitas Tarumanagara, 2025)
This research aims to obtain empirical evidence regarding the effect of Leverage (LEV), and Corporate Governance (TK) on Earning Management (EM) with Tax Avoidance (TA) as a moderation variabel of Manufacturing company listed on BEI during 2018-2021. Sample was selected using purposive sampling method and uses secondary data in the form of financial reports obtain from the website www.idx.co.id. The total sample used was 216 data. Data processing techniques use multiple linear regression using Eviews 12.0 and Microsoft Excel 2019. The results of this study indicate that LEV and TK have positive but non significant effect to EM. TA reinforce LEV effect on EM. TA weakens TK effect on EM. The implication of this study is to see companies’ movement regarding earnings management, after covid-19 pandemic in Indonesia subsided.